Theriogenology 2017
DOI: 10.5772/intechopen.69091
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of the Heat Stress Impact in Livestock Reproduction

Abstract: Heat stress affects the fertility and reproductive livestock performance by compromising the physiology reproductive tract, through hormonal imbalance, decreased oocyte quality and poor semen quality, and decreased embryo development and survival. Heat stress decreases the secretion of luteinizing hormone and estradiol resulting in reduced length and intensity of estrus expression, increased incidence of anoestrus and silent heat in farm animals. Oocytes exposed to thermal stress lose its competence for fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 81 publications
2
26
0
2
Order By: Relevance
“…It was found that the decrease in ST as the FSF inclusion levels increased in Dohne Merino rams were the direct effect of FSF during the experiment. The result from this study aligned with the report of ( Krishman et al., 2017 ) that observed that, dietary supplementation of trace elements to animal feeds can ameliorate adverse effect of heat stress. Since, FSF is abundantly rich in about 14 trace elements, the addition of FSF to Dohne Merino rams’ diet can be concluded to reduced ST in FSF supplemented diet compared to FSF non-supplemented diet.…”
Section: Discussionsupporting
confidence: 90%
“…It was found that the decrease in ST as the FSF inclusion levels increased in Dohne Merino rams were the direct effect of FSF during the experiment. The result from this study aligned with the report of ( Krishman et al., 2017 ) that observed that, dietary supplementation of trace elements to animal feeds can ameliorate adverse effect of heat stress. Since, FSF is abundantly rich in about 14 trace elements, the addition of FSF to Dohne Merino rams’ diet can be concluded to reduced ST in FSF supplemented diet compared to FSF non-supplemented diet.…”
Section: Discussionsupporting
confidence: 90%
“…& The future climate scenario analyses indicate that the length of consecutive days of heat stress for dairy cattle with THI higher than the severe/danger threshold is likely to increase in future periods in WA. These changes are also important because the severity of heat stress impact on milk production would increase by increasing the length of heat stress period (Rojas-Downing et al 2017;Krishnan et al 2017). & Based on GFDL-ESM2M, HadGEM2-ES, and MPI-ESM-MR projections under the RCP4.5 scenario, by 2071-2100, around 2.0, 5.8, and 9.8% of dairy cattle population in WA would experience dangerous heat stress events 40% (~145 days) more frequent than the historical period, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The average BW of Brahman Cross cattle was 35 kg (Holmes et al, 1992), Zebu-Wagyu crosses were 28 kg (Hearnshaw et al, 2001), and Zebu-Belgian Blue crosses were 35 kg (Nogueira et al, 2016). Average cattle BW in this study tends to be smaller due to environmental factors, high temperatures as in tropical environments will reduce birth weight compared to temperate environments (Krishnan et al, 2017).…”
Section: Resultsmentioning
confidence: 56%